Elementary school students' naïve conceptions and misconceptions about energy in physical education context. Issue 1 (2nd January 2019) - Zhang, Tan; Chen, Ang; Ennis, Catherine
ABSTRACT: The purpose of this study was to explore and reveal naïve conceptions and misconceptions about energy embedded in elementary school students' prior knowledge. Students' performance on standardized knowledge test was used to classify students into low, median and high levels of knowledge about the cardiovascular system. Semi-structured in-depth interviews were conducted with students in each group to extract their understanding of energy in relation to food choices, physical activities, and exercises. Analysis of the interview data generated six categories of naïve conceptions and two categories of misconceptions. Different conceptual change theories, including Chi's ontological change theory, Ohlsson's resubsumption theory, and enculturation theory were used to analyze and understand these naïve conceptions and misconceptions and why they could be robust to change. The analyses confirm the need to adopt a multi-theoretical approach to the understanding of students' naïve conceptions and misconceptions (Chinn & Samarapungavan, 2009. Conceptual change-multiple routes, multiple mechanisms: A commentary on Ohlsson. Educational Psychologist, 44 (1), 1–10). The findings encourage physical and health educators adopt different strategies to address the potential learning obstacles brought by students' naïve conceptions and misconceptions.